Tyranny: a study in the abuse of power - Latey, Maurice (London, 1969)
This book he compares them with their great predecessors, from the first wave of Greek tyrants in the 7th and 6th centuries B.C., through the Roman Empire and mediaeval times, with the Renaissance despots and with the first modern nationalist dictator, Napoleon.
Keywords: Despotism